PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS WEB WORDPRESS PADA MATERI DIAGRAM LINGKARAN KELAS IV SDN DAWUHANLOR - Merita Dewi Anggraini; Wahid Ibnu Zaman; Bagus Amirul Mukmin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low learning outcomes of students in elementary schools are caused by the lack of optimal use of learning media. So there is a need to develop learning media that can attract students' interest in learning, especially in mathematics lessons with circle diagram material, such as the development of WordPress web-based learning media. The aims of this research are (1) to determine the validity of web-based mathematics learning media using WordPress on circle diagram material, (2) to determine the practicality of web-based mathematics learning media using WordPress on circle diagram material, (3) to determine the effectiveness of web-based mathematics learning media by using WordPress on circle diagram material. This research uses the R&D (Research & Development) method with five stages of the ADDIE model, namely Analysis, Design, Development, Implementation, Evaluation. The subjects in this research were fourth grade students at SDN Dawuhanlor, Kec. Purwoasri, Kab. Kediri with 5 limited trial students and 16 wide trial students. The results of this research are (1) Media validity from media experts obtained a score of 93% with very valid criteria, and material experts obtained a score of 90% with very valid criteria. (2) The practicality of the media obtained a score of 77% with practical criteria from the teacher's response, while the student responses obtained a score of 92% with very practical criteria in limited trials, and obtained a score of 93% with very practical criteria in extensive trials. (3) The effectiveness of the media in the limited trial obtained a score of 56% from the pre-test results and obtained a score of 98% from the post-test results, while in the extensive trial it obtained a score of 41% from the pre-test results and obtained a score of 95% from the post-test results. Therefore, researchers hope that this research can be used as a reference for future research.